2003
DOI: 10.1086/345307
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Gill Metabolic Potential as a Function of Salinity in the Euryhaline Crab,Callinectes sapidusRathbun

Abstract: The body-size scaling pattern of enzymes that are important in energy metabolism was examined in gills of the blue crab as a function of acclimation salinity. We hypothesized that the higher surface-area-to-volume ratio of small crabs would impose a greater metabolic cost for hyperosmoregulation, leading to an increase in the capacity for ATP production in gills. Postmetamorphic crabs spanning a 2,500-fold range in body mass were examined following a 7-d exposure to a salinity of 35, 17, or 5 ppt. The posterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Crabs 5 g and less had uniformly high levels of gill Na 1 ,K 1 -ATPase (both in anterior and posterior gills), while those greater than 5 g had much lower levels. This pattern was also observed by our collaborators (Kinsey et al, 2003) in several metabolic enzymes in the gills of blue crabs. Arginine kinase from posterior gills and b-hydroxyacyl-CoA dehydrogenase from anterior and posterior gills also displayed uniformly high activities in small crabs with a dramatic decrease in activity in larger crabs.…”
Section: Gill Permeabilitysupporting
confidence: 87%
“…Crabs 5 g and less had uniformly high levels of gill Na 1 ,K 1 -ATPase (both in anterior and posterior gills), while those greater than 5 g had much lower levels. This pattern was also observed by our collaborators (Kinsey et al, 2003) in several metabolic enzymes in the gills of blue crabs. Arginine kinase from posterior gills and b-hydroxyacyl-CoA dehydrogenase from anterior and posterior gills also displayed uniformly high activities in small crabs with a dramatic decrease in activity in larger crabs.…”
Section: Gill Permeabilitysupporting
confidence: 87%
“…The potential metabolic cost could be masked in the results from this study because of the remarkable ability of blue crabs to regulate their internal chemistry (Towle et al 1976, Henry & Kormanik 1985, Mangum et al 1985. It is also possible that the metabolic cost is constrained to only the gills in blue crabs, as has been observed in juvenile blue crabs exposed to an osmotic gradient in the study by Kinsey et al (2003). In that study, citrate synthase activity was significantly higher in the gill tissue of juvenile crabs exposed to low salinity than in the gill tissue of their adult counterparts, but no overall effect on the capacity for energy metabolism was observed.…”
Section: Discussionmentioning
confidence: 78%
“…Another possible factor associated with the resistance to the freshwater stress test is the shrimp's ability to use fatty acid as energy in their gills to facilitate ion pumping (Kinsey et al. ; Palacios and Racotta ). Previous research by Palacios and Racotta (), Palacios et al.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible factor associated with the resistance to the freshwater stress test is the shrimp's ability to use fatty acid as energy in their gills to facilitate ion pumping (Kinsey et al 2003;Palacios and Racotta 2007). Previous research by Palacios and Racotta (2007), Palacios et al (2004), and Morris et al (1982) indicated that fatty acid content may affect water and ions permeability, which in turn can determine how shrimps respond to freshwater stress.…”
Section: Fatty Acidsmentioning
confidence: 99%